Development of a plasmid free CRISPR-Cas9 system for the genetic modification of Mucor circinelloides. Issue 1 (December 2017) - Nagy, Gábor; Szebenyi, Csilla; Csernetics, Árpád; Vaz, Amanda; Tóth, Eszter; Vágvölgyi, Csaba; Papp, Tamás
Abstract Mucor circinelloides and other members of Mucorales are filamentous fungi, widely used as model organisms in basic and applied studies. Although genetic manipulation methods have been described for some Mucoral fungi, construction of stable integrative transformants by homologous recombination has remained a great challenge in these organisms. In the present study, a plasmid free CRISPR-Cas9 system was firstly developed for the genetic modification of a Mucoral fungus. The described method offers a rapid but robust tool to obtain mitotically stable mutants ofM .circinelloides via targeted integration of the desired DNA. It does not require plasmid construction and its expression in the recipient organism. Instead, it involves the direct introduction of the guide RNA and the Cas9 enzyme and, in case of homology directed repair (HDR), the template DNA into the recipient strain. Efficiency of the method for non-homologous end joining (NHEJ) and HDR was tested by disrupting two different genes, i.e.carB encoding phytoene dehydrogenase andhmgR2 encoding 3-hydroxy-3-methylglutaryl-CoA reductase, ofM .circinelloides . Both NHEJ and HDR resulted in stable gene disruption mutants. While NHEJ caused extensive deletions upstream from the protospacer adjacent motif, HDR assured the integration of the deletion cassette at the targeted site.